2023
DOI: 10.1371/journal.pone.0280089
|View full text |Cite
|
Sign up to set email alerts
|

Mental health care in the city of Lubumbashi, Democratic Republic of the Congo: Analysis of demand, supply and operational response capacity of the health district of Tshamilemba

Abstract: Background Integrating mental health care into the primary care system is an important policy option in the Democratic Republic of the Congo (DRC). From the perspective of the integration of mental health care in district health services, this study analyzed the existing demand and supply of mental health care in the health district of Tshamilemba, which is located in Lubumbashi, the second largest city of the DRC. We critically examined the district’s operational response capacity to address mental health. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 28 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Behavioural problems were associated with socioeconomic features only 3 34. Mukala, Mayolo E. 2023 41 Lubumbashi, DRC 591 residents responded and conducted 5 focus groups with 50 key stakeholders (doctors, nurses, managers, community health workers. and leaders, health care users) Integrating mental health care into the primary care system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioural problems were associated with socioeconomic features only 3 34. Mukala, Mayolo E. 2023 41 Lubumbashi, DRC 591 residents responded and conducted 5 focus groups with 50 key stakeholders (doctors, nurses, managers, community health workers. and leaders, health care users) Integrating mental health care into the primary care system.…”
Section: Resultsmentioning
confidence: 99%
“…There are very few hospitals for the treatment of mental health disorders in DRC. The country has only six public psychiatric hospitals, and a dozen private mental health centres with 500 beds for nearly 90 million inhabitants, almost all of which are in big cities 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…At the personal and household level, we found that the general population does not have the needed skills for self-care in case of mental health problems. At the community level, where stigmatization prevails [14], people with unmet mental health needs resort essentially to spiritual and traditional healers, as there are no community-based organizations, no school-based services, no youth clubs, no user associations, etc., taking care of mental health patients. At the primary care level, we found that no health centers or district hospitals are currently offering mental health care.…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs, where social protection is limited, nancial support from the family is of great relevance. Because stigmatizing attitudes toward patients with mental disorders are highly visible in urban areas of the DRC [14], family caregivers of patients with mental illness may also be exposed to stigma. Among the strategies to reduce stigma for family caregivers, i.e., improving mental health literacy, education and coping strategies, promoting well-being, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation